Evaluation of a Multimodal Sensory Feedback Device for Displaying Proprioceptive Data from a Robotic Grasper - Molina, Alicia; Kelly, Erin; Majditehran, Houriyeh; Hammond, Frank L. (IEEE RO-MAN, 2023)
A wearable multimodal sensory feedback device (SFD) was developed to communicate proprioceptive information from a robotic grasper onto the operator's forearm. The robotic grasper could pick up objects through a pinching motion and was composed of two fingers, each able to open and close in a mirror of the other. The aperture amount of each of the grasper's fingers was mapped onto the SFD which uses two separate actuators that induced skin-stretch and implemented vibrotactile stimuli to communicate this information to the user. This paper evaluates the extent to which the SFD can effectively communicate the grasper's proprioceptive information using skin stretch feedback that is maintained with vibrations. Subjects were asked to manipulate the grasper blindly guided by their natural proprioceptive feedback only (NO), their natural proprioceptive feedback and skin-stretch feedback (NS), skin-stretch feedback only (SS), and skin-stretch and vibrotactile stimulation (SV). The experiments' results indicate that the SFD can effectively communicate proprioceptive sensory information and enhance the body's natural proprioceptive sense.